The influence of water quality factors on the effectivity of a synthetic pyrethroid insecticide - Stiller, M.(Michael) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1987.